Phenolic and amino acid profiles, and antioxidant properties of third generation snack foods adding Citrus mitis by-products and milk powder: impact of extrusion processing and microwave-heating “Impact of processing on obtaining healthy snacks” - Xóchitl Ariadna Ruiz-Armenta; Carlos Iván Delgado-Nieblas; José de Jesús Zazueta-Morales; Ernesto Aguilar-Palazuelos; Perla Rosa Fitch-Vargas; José Alberto Gallegos-Infante; José Ángel López-Valenzuela; María Fernanda Quintero-Soto (Emirates Journal of Food and Agriculture)
Currently, there is a high consumption of snack foods worldwide, suggesting the improvement of their nutritional/nutraceutical properties by adding raw materials rich in bioactive compounds. This work aimed to study the impact of the processing stages on phenolic and amino acid profiles and the antioxidant properties of extruded snack foods by adding Citrus mitis by-products and milk powder. The color parameter C*, phytochemical, and antioxidant properties of four formulations were evaluated in the processing stages: unprocessed mixture (PS1), extruded pellets (PS2), and microwave-expanded products (PS3). The statistical analysis was performed using an unifactorial design with three levels (PS1, PS2, and PS3), evaluating four formulations (F1–F4) and a commercial product (COM). The mean values of the response variables were compared using the Fisher test (p ≤ 0.05). Color parameter C* increased in PS3 concerning the PS2 and PS1 processing stages. Total flavonoid content (TFC), hydroxyl radical scavenging activity (HRSA), and inhibition of human LDL oxidation (ILDLox) decreased in PS2 regarding PS1. Likewise, TFC decreased in PS3 regarding PS2, whereas HRSA and ILDLox increased. PS3 exhibited higher TFC, HRSA, and ILDLox values in all formulations regarding commercial snack foods. Sixteen phenolic acids, nine flavonoids, and a hydroxy acid were identified in free and bound extracts by UPLC coupled to ESI-MS. The amino acid profile was affected by processing, and Lysine showed the lowest stability. The microwave-expanded snack foods had acceptable sensory properties evaluated by consumers, and adding raw materials rich in phytochemical compounds and high-quality proteins enhanced their nutraceutical/nutritional properties.